The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0150372
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability Associated with p53 Knockdown in the Generation of Huntington’s Disease Human Induced Pluripotent Stem Cells

Abstract: Alterations in DNA damage response and repair have been observed in Huntington’s disease (HD). We generated induced pluripotent stem cells (iPSC) from primary dermal fibroblasts of 5 patients with HD and 5 control subjects. A significant fraction of the HD iPSC lines had genomic abnormalities as assessed by karyotype analysis, while none of our control lines had detectable genomic abnormalities. We demonstrate a statistically significant increase in genomic instability in HD cells during reprogramming. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…RLIC treatment alters the expression of multiple genes and proteins, including hypoxia-inducible factor-1α (HIF-1α), HIF-1β , the anti-apoptotic gene Bcl-2, and superoxide dismutase (SOD), all of which are observed to be elevated. RLIC has also been observed to inhibit the expression of the apoptotic protein, p53 (Jin et al, 2016;Salido et al, 2013;Tidball et al, 2016). These changes can affect a range of processes, such as improving the metabolism of nerve cells, inhibiting oxidative damage, and reducing neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…RLIC treatment alters the expression of multiple genes and proteins, including hypoxia-inducible factor-1α (HIF-1α), HIF-1β , the anti-apoptotic gene Bcl-2, and superoxide dismutase (SOD), all of which are observed to be elevated. RLIC has also been observed to inhibit the expression of the apoptotic protein, p53 (Jin et al, 2016;Salido et al, 2013;Tidball et al, 2016). These changes can affect a range of processes, such as improving the metabolism of nerve cells, inhibiting oxidative damage, and reducing neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the non-integrative methods for iPSC production, episomal plasmids have been a popular choice due to their relatively lower costs and simplicity of use. One of the few caveats of this expression system is that the episomes currently used by most groups contain immortalization factors, such as large T antigen (Yu et al, 2009) or shRNA for p53 knockdown (Okita et al, 2011), which in some cases have been shown to cause genomic instability (Schlaeger et al, 2015;Tidball et al, 2016). In addition, episomal plasmid expression may persist in up to 33% of the reprogrammed cells even after P11 (Okita et al, 2011;Schlaeger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Skin punch biopsies were obtained from 3 EIEE13 patients (P1-3) and two healthy controls (C1 and C4) without known genetic disorders with consent under a protocol approved by the Institutional Review Board of Michigan Medicine and reprogrammed by previously published methods (Tidball et al, 2017). Two additional control lines used in this study were previously reported as CC1 (now C2) and CHD2 WT/WT2 (now C3) from (Tidball et al, 2016;Tidball et al, 2017), respectively, and were reprogrammed using identical methods. See Supplemental materials for further details of reprogramming and cell line validation.…”
Section: Induced Pluripotent Stem Cell Reprogrammingmentioning
confidence: 99%
“…1A). We used two additional control lines, C2 and C3, ( Table 1) that have been previously published (Tidball et al, 2016;Tidball et al, 2017). Each line used for subsequent experiments was negative for episomal reprogramming vector integration, had no observable genomic abnormalities as tested by either g-band karyotype or SNP chip microarray analyses, and expressed markers of pluripotency ( Supplemental Fig.…”
Section: Eiee13 Patient-derived Neurons Show Variant-specific Differementioning
confidence: 99%